The Relationship Between The Implementation of Safety Briefing and Worker Safe Behavior at Pt Pln Up Gresik - Agnes Dwi Shavitri; Sestiono Mindiharto (Jurnal Ners, 2026)
The prevention of occupational illnesses and accidents is an essential part of every industrial operation's Occupational Safety and Health (OHS) plan. Safety briefings are a part of the company's strategy to raise awareness of the importance of safety on the job. The purpose of this research is to ascertain whether or not PT. PLN Nusantara Power UP Gresik's safety briefings had an effect on employees' safety practices. The research methodology employed in this study was quantitative and based on correlations. Employees of PT. PLN Nusantara Power UP Gresik made up the study's population, and a sampling strategy that was suitable for the population's characteristics was used to identify the sample. Questionnaires consisting of indicators of safety briefing implementation and worker safety behavior were sent in order to gather data. In order to find the relationships between the variables, statistical analysis was used to the collected data. There was a favorable and statistically significant correlation between workers' safety behavior and the introduction of safety briefings, according to the data. This suggests that the degree of worker safety behavior is directly proportional to the efficacy of safety briefings. Therefore, PT. PLN Nusantara Power UP Gresik's safety briefings might be a useful tool for fostering a safer work environment.